An experimental evaluation of mango peel extract and soapberry extract as natural stain removal agents on cotton fabric - Sibug, Mikhaella B.
Saponin is a biosurfactant known for its cleaning and foaming properties and is found in certain plants in the Philippines such as mango and soapberry. This experimental study explored the effectiveness of mango peel and soapberry extracts in removing common stains, like coffee and oil, from white woven cotton fabric. The extracts were produced through decoction method. Cotton fabric swatches were divided into 6 treatment groups: 1.) coffee-stained swatches washed with water only; 2.) oil-stained swatches washed with water only; 3.) coffee-stained swatches washed with soapberry extract; 4.) oil-stained swatches washed with soapberry extract; 5.) coffee-stained swatches washed with mango peel extract; and 6.) oil-stained swatches washed with mango peel extract. Each treatment group was subjected to 30-minute wash using a portable turbine. After drying, each treated swatch was photographed and uploaded into an image-processing software. To quantify the amount of stain removed, the Mean Gray Values (MGV) of the treated stain area were determined and compared to the MGV of the unstained area to formulate its Brightness Ratio. Through statistical analysis, results showed that Group 6 had the highest mean Brightness Ratio of 0.969 and then Group 4 had 0.961. Meanwhile, Group 1 and 2 had lower ratios of 0.944 and 0.951. Although complete stain removal was not achieved, mango peel and soapberry extracts exhibited a degree of stain-lightening effect. In response to environmental concerns with chemical detergents, they can be further developed as natural alternatives. The study recommends standardizing the saponin extraction and wash test in future experiments. Color spectrometry can also be explored to quantify the changes in the stains before and after treatment.